1979
DOI: 10.1088/0022-3727/12/3/010
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the wavelength dependence of the threshold of laser-induced gas breakdown

Abstract: Measurements of the threshold intensity for breakdown over the wavelength range 720-840 nm have been made at atmospheric pressure in several gases, by means of a high output power laser pumped, tunable dye laser. Although it may be expected that the resonant phenomena observed in earlier experiments would be more pronounced at lower pressures, the authors have found that over the entire wavelength range studied, the results showed the direct dependence on both wavelength and pulse duration predicted by cascade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
(8 reference statements)
3
19
0
Order By: Relevance
“…It also comprises the loss terms due to vibration excitation, molecular dissociation besides the electron loss processes through electron recombination. Under the experimental conditions considered in this analysis [5], superelastic collisions from the electronically and vibrationally excited states, as well as radiative recombination of the hydrogen molecule are neglected. Dissociative attachment from the vibrationally excited molecules is also ignored.…”
Section: Basic Equationmentioning
confidence: 99%
See 4 more Smart Citations
“…It also comprises the loss terms due to vibration excitation, molecular dissociation besides the electron loss processes through electron recombination. Under the experimental conditions considered in this analysis [5], superelastic collisions from the electronically and vibrationally excited states, as well as radiative recombination of the hydrogen molecule are neglected. Dissociative attachment from the vibrationally excited molecules is also ignored.…”
Section: Basic Equationmentioning
confidence: 99%
“…Although a considerable bodies of study on laser induced breakdown in gases have been reported (see for example [1][2][3][4][5][6][7][8]), the breakdown phenomenon of common combustion gases such as hydrogen has not been available. Because of the importance of such phenomenon, in various applications it attracted the attention of many researchers, in particular the mechanism that convert the laser energy to thrust energy or mechanical energy that could be approached via high power laser produced plasma (LPP) in a gas breakdown process [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations